Language and other complex behaviors: Unifying characteristics, computational models, neural mechanisms. (July 2017) - Edelman, Shimon
Abstract: Similar to other complex behaviors, language is dynamic, social, multimodal, patterned, and purposive, its purpose being to promote desirable actions or thoughts in others and self (Edelman, 2017b). An analysis of the functional characteristics shared by complex sequential behaviors suggests that they all present a common overarching computational problem: dynamically controlled constrained navigation in concrete or abstract situation spaces. With this conceptual framework in mind, I compare and contrast computational models of language and evaluate their potential for explaining linguistic behavior and for elucidating the brain mechanisms that support it. Highlights: Like other complex behaviors, language is dynamic, social, multimodal, patterned, and purposive. The purpose of language is to promote desirable actions or thoughts in others and self. All complex sequential behaviors present a common overarching computational problem: dynamically controlled constrained navigation in concrete or abstract situation spaces. A classification of computational models of language is offered and classes of models evaluated.